Latest research on the Iberian Peninsula warrior and diadem stelae (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
Despite being known for more than 120 years, the western Iberian Peninsula stelae continue to generate debate and no consensus has been reached on their purpose. For this reason, its study and analysis continue to flourish within proto-historical studies.A brief review of this field latest research currently shows us five main working lines, in addition to traditional iconographic studies. These are: archaeological survey, an increasingly common use of GIS, photography and creation of digital models, petrological studies and engraving techniques and carving instrumental studies.Finally, the Instituto de Arqueología-CSIC working protocol for stelae review and study is defined.
Keywords: Historiography of the stele of the Western peninsula; New technologies in archeology; GIS; Archaeological photography; Geoarchaeology; Warrior and diadem stele